Pemanfaatan Cocopeat dan Pasir Untuk Bertanam Sawi Pakcoy Dengan Media Tanam Box Kayu di Lahan Sempit Dilengkapi Penyiraman Model Sprinkle Sprayer Otomatis Bagi Kelompok PKK Melati Desa Talang Pauh Kelapa Bengkulu Tengah - Halauddin; samdara, rida; Suhendra (Indonesian Journal of Community Empowerment and Service (ICOMES), 2024)
This Community service activities have been carried out for the Science and Technology Faculty of Mathematics and Natural Sciences, Bengkulu University with the title: "Using Cocopeat and sand to plant Pakcoy mustard greens using wooden box planting media in narrow land equipped with automatic sprinkle sprayer model watering for the family welfare program Melati group, Talang Pauh Kelapa Village, Central Bengkulu". This science and technology service activity aims to provide additional knowledge to the family welfare program Melati Group to be able to cultivate Pakcoy mustard plants using Cocopeat and sand planting media in wooden boxes as well as installing and using a rotating garden model Sprinkler Sprayer watering tool to maintain the stability of the watering system so that it is even and watering system no longer conventional. From the results of the implementation of the science and technology service at the Faculty of Mathematics and Natural Sciences, Bengkulu University in 2024, the target audience, in this case the family welfare program Melati group, Talang Pauh Village, was able to cultivate Pakcoy mustard plants using Cocopeat and sand planting media in wooden boxes as well as installing and using a garden model Sprinkler Sprayer watering tool.